Exploring the relationship between personality traits and sexual harassment in Indonesian university students - Rahmawaty, Patria; Zulkarnain, Zulkarnain; Riyanto, Andra Ade (Intelektual Pustaka Media Utama, 2025)
Sexual harassment in educational institutions has long been a global concern. Various studies on sexual violence have been carried out, but research on personality, power, and moral disengagement, which are associated with sexual harassment behavior among students in higher education, was still limited. Therefore, this research aims to investigate the influence of personality, power, and moral disengagement on sexual harassment behavior among students in higher education. This research involved 403 students from 5 universities in Balikpapan City, East Kalimantan Province, Indonesia. We used structural equation modelling (SEM) analysis to test the influence of each variable. According to the research's findings, moral disengagement, and personality both have a direct impact on sexual harassment. In addition, moral disengagement has been proven to be able to mediate between power and sexual harassment. The results of this research provide important implications for public policy makers in higher education, practitioners, researchers, and the public in identifying factors of sexual harassment among students in higher education.